O acesso aos instrumentos públicos como influenciador do consumo cultural pela população de baixa renda - Alexandre Rabelo; Danielle Miranda de Oliveira Arruda Gomes; Áurio Lúcio Leocádio (Ciências Sociais Unisinos)
This research project aimed at analyzing the relationships between the influential vari- ables and the consumption of cultural products by low-income consumers, considering the model adapted from Leocádio (2008). In this context, we sought to identify variables that explain the consumption of cultural products; to assess the relationship between the access to public instruments of cultural consumption and the consumption of cul- tural products; to assess the relationship between the consumer’s income profile and the consumption of cultural products; to assess the relationship between the consumer’s profile of cultural capital and the consumption of cultural products; and to examine the relationships between the background elements, on the basis of the model adapted from Leocádio (2008), that influence the consumption of cultural products. We presented a model that integrates the history of cultural consumption. We used the Survey as a method and applied it to 556 respondents in 31 neighborhoods of the city of Fortaleza with low income consumers of cultural products. We employed techniques for data analysis using multivariate factor analysis, as well as structural equation modeling using the software Smartpls 2.0. The background elements that related to the consumption were cultural capital, preference and the influence of reference groups. The structural model analysis demonstrated that innovativeness, access to consumption instruments and experiences in artistic events influence the consumer’s preference and have no relation to the con- sumption of cultural products.